(untitled) (EAAE Annual Conference Proceedings, 2023)
The participation of society in public spaces issues, though advocated for decades, experiences an increase in recent years. Citizen participation in Croatian spatial planning appears to be mostly declarative and formally takes place in the final stages of planning. On the contrary, the full benefits of integrative planning would be if participation of all sectors (civil, academic, economy and management structures) is continuous, especially important in the initial planning phase - forming the basic intentions.